1994
DOI: 10.1016/0735-1097(94)90878-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acutely altered loading conditions on left atrial appendage flow velocities

Abstract: These results indicate that 1) both the magnitude and the pattern of left atrial appendage emptying and filling velocities are dependent on loading conditions, and 2) left atrial appendage velocities are influenced to a greater extent by changes in left ventricular than in left atrial appendage function. These findings may have implications for the pathogenesis of left atrial appendage thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 13 publications
7
49
0
Order By: Relevance
“…Because the LA appendage compliance is higher than LA main chamber compliance, the LA appendage contributes to LA reservoir function [66][67][68]. When LA pressure increases below a certain level, the LA appendage volume gradually increases, and the peak atrial systolic velocity of LA appendage flow is increased.…”
Section: La Appendage Functionmentioning
confidence: 99%
“…Because the LA appendage compliance is higher than LA main chamber compliance, the LA appendage contributes to LA reservoir function [66][67][68]. When LA pressure increases below a certain level, the LA appendage volume gradually increases, and the peak atrial systolic velocity of LA appendage flow is increased.…”
Section: La Appendage Functionmentioning
confidence: 99%
“…Mitral annu lus motion as well as left ventricular relaxation were pro posed to have influence on the diastolic LAA forward flow [15]. However, from a transesophageal echocardiographic study on atrial paced dogs with simultaneous measure ment of the pressure and dimension in the left atrium and left ventricle, Hoit et al [16] emphasized the influence of left ventricular relaxation function on the early LAA emptying flow.…”
Section: Influence O F Ventricular Relaxation and Filling On Laa Flowmentioning
confidence: 99%
“…Pop et al [24] also demonstrated that patients with a larger transmitral inflow velocity-time integral had less incidence of left atrial SEC. As the LAA flow velocity is influenced by the loading condition of the left atrium [25], the increased left atrial pressure secondary to the increased left ventricular end-diastolic pressure might also play a role in the attenuation of LAA outflow in the patients with impaired left ventricular function.…”
Section: Effect O F Left Ventricular Function On Laa Outflowmentioning
confidence: 99%